Structural analysis and fluid geochemistry as tools to assess the potential of the Tocomar geothermal system, Central Puna (Argentina). (January 2022) - Filipovich, Rubén; Chiodi, Agostina; Báez, Walter; Ahumada, Maria Florencia; Invernizzi, Chiara; Taviani, Sara; Aldega, Luca; Tassi, Franco; Barrios, Alfonso; Corrado, Sveva; Groppelli, Gianluca; Norini, Gianluca; et al.
Highlights: An integrated conceptual model of the Tocomar Geothermal system is presented. Compositional data of thermal fluids along with structural, Raman spectroscopic, and in-situ permeability data from the Tocomar Geothermal area are reported. Cation geothermometers indicates reservoir temperatures up to 235 °C. The structural control on flow pathways and fluids-rock interaction processes are discussed. The geothermal electric potential is stochastically assessed. Abstract: The Argentinean Andean region hosts a vast geothermal resource clustered by active magmatic and tectonic activity. One of the most studied geothermal areas is the Tuzgle-Tocomar geothermal system in Central Puna (NW Argentina). However, despite the existence of several studies since the 1970′s highlighting the geothermal potential of the area, only highly schematic and dissimilar conceptual models have been proposed for the Tocomar Geothermal System. This study presents new detailed geological-structural and hydrogeochemical data, together with in-situ permeability analysis of fault zones and Raman spectroscopic characterization of hydrothermal-alteration minerals. The electrical generating capacity has also been evaluated using the volumetric method and a stochastic approach. A new comprehensive conceptual model of the studied area was constructed highlighting the role of the Calama-Olacapato-El Toro (COT) fault-system in the circulation of hydrothermal fluids. The reservoir of the Tocomar geothermal system has a Na + -Clˉ(HCO3 )ˉ composition and an estimated temperature of ∼235 °C. Such a reservoir is hosted in fractured Ordovician rocks and controlled by the COT-like Chorrillos transpressive fault at 1000–1500 m depth b.g.l. The water isotopic data and hydrological features indicate a regional recharge beyond the Tocomar sub-basin boundaries (>5000 m a.s.l.). Additionally, the main hydrothermal reservoir receives inputs of magmatic fluids from the degassing of the intra-crustal rhyolitic magma chamber of the Tocomar volcanic center. The Monte Carlo simulations suggest that the Tocomar geothermal system has a probable power production capacity above 1.23 MWe (P90), 6.18 MWe (P50) and 11.67 MWe (P10) at different confidence levels. All calculations were biased towards minimum values, thus a tighter definition of the resource size and fracture porosity would significantly impact on the predictions. Notwithstanding, the strategic position of the Tocomar geothermal field encourages move forward towards more in-depth exploration phases.